Stand structure of 1-ha logged-over Bornean forest in Universiti Putra Malaysia Bintulu Campus, Sarawak, Malaysia - Lepun, Philip; Sait, Muaish; Rosli, Zamri; I., Faridah Hanum (Malaysian Nature Society, 2021)
All remaining forest areas in Universiti Putra Malaysia Bintulu Sarawak Campus are lowland logged-over mixed dipterocarp forest. The tree species diversity is high with 232 species belonging to 111 genera and 43 families per ha. The family Dipterocarpaceae contributes about one-fifth the total number of trees found here and is the most speciose family with 41 species contributing a basal area of 9.64 m2 and volume of 230.91 m3 per ha. The tree stand composition shows the forest is still in the process of regeneration with over 90% of the total trees having a diameter at breast height of less than 40 cm. This forest plays an important role in the teaching and learning for undergraduates taking the forestry programme.